CFO Effort and Public Firms' Financial Information Environment* - Biggerstaff, Lee E.; Cicero, David C.; Goldie, Brad; Reid, Lauren C.; Ge, Weili; Moon, Keehea (Contemporary Accounting Research, 2021)
ABSTRACT We test the association between CFO effort and the quality of public firms' financial information environments. We evaluate this relation using a measure of CFO leisure consumption—specifically, the amount of golf played—as an inverse proxy for effort. We find a negative relation between CFOs' compensation incentives and golf play, suggesting they exert more effort when they have greater incentives to increase firm value. High CFO leisure consumption is associated with lower earnings quality, less accurate earnings guidance, and reduced CFO conference call participation. Additionally, CFO leisure appears to affect external monitors, as it is associated with greater analyst forecast dispersion and increased audit fees. We do not find similar relations when evaluating the amount of golf played by CEOs, suggesting the unique importance of CFO effort in the financial reporting process.